Geology and petrology of the Frade alkaline mafic-ultramafic layered complex in the São Sebastião Island, Southeastern, Brazil - Giraldo Arroyave, Maria Isabel (2020)
The Frade Alkaline Mafic-Ultramafic Layered Complex crops out to south of the São Sebastião Island on the north coast of the state of São Pablo State (Brazil). It is a small plutonic intrusive with a ring sill-like shape and a maximum thickness estimated in 350 m, associated with younger ultramafic and felsic dikes, and - micro olivine clinopyroxenites and micro (mela) gabbros as dikes, sills and enclaves. Geochronological estimations indicate that emplacement took place at 88 Ma at shallow crustal level, around 2-3 km, liquidus temperature about 1050°C; the late crystallization suggests close-to-solidus temperature of ~870°C in average. The high temperature promoted a contact aureole in the host porphyritic granodiorites, evidenced in the development of recrystallization textures and granophyric intergrowths as well as orthopyroxene development and chemical and isotopic exchange in the contact zone. The mafic intrusive displays well-developed layered structures at the base of the sequence that vary to a strong mineral lamination upwards. The structures, textures, as well as the cumulus and intercumulus mineralogy allow recognizing 4 main gabbroic units, which, from the bottom to the top, are: 1) Lower Gabbro Sequence (LGS); 2) Intermediate Gabbro Sequence (IGS); 3) Upper Gabbro Sequence (UGS); 4) Massive Leucogabbros (MLG). It is thought that the rocks from the LGS, IGS, and UGS were formed from the same magma batch undergoing fractional crystallization and modification of the main ferromagnesian minerals by interaction with the intercumulus liquid. Crystallization is accompanied by minor crustal contamination reflected in the progressive increase in the 87Sr/86Sri isotope composition in plagioclase and apatite through stratigraphy coupled with depletion in the 143Nd/144Ndi over apatite. The Massive Leucogabbros represent a period of recharge by a less evolved and less contaminated magma keeping the chemical and isotopic signatures of the common source with the Frade Intrusive. In this rock, the intercumulus mafic assemblage probably was formed by the interaction of the resident magma with the primitive melt. Associated to the Frade Intrusion, ultramafic (picrite and micro peridotite) and melanocratic porphyritic subvolcanic rocks have been recognized in the form of dikes, sills and enclaves. The relationship of these porhyritic melanocratic rocks and the main intrusive is given by the similarities in the chemical characteristics of the main mineral phases, but also the isotopic Sr composition of plagioclase. Detailed chemical analysis allowed to characterize the different crystal population. Macrocryst of pyroxene were defined as MC1 and MC2. In the porphyritic clinopyroxenites, MC1 cores are mostly antecryst Crdiopsides recycled from a source located at a depth of ~8 km. MC2 macrocryst are Al-diopsides phenocryst crystallized in a magma chamber located at a depth of ~6 km, which is probably the same magmatic source of the Frade Intrusive. MC2 phenocrysts define an evolutionary trend with rims and groundmass pyroxenes by progressive fractional crystallization during magma ascent and emplacement in a shallow magma chamber located ~3 km depth, the Frade magma chamber. Olivine macrocryst show a well differentiation path with the groundmass crystals. If they were antecryst they re-equilibrated with the host magma that formed the Frade Mafic Intrusive. The chemical and isotopic differences in the picrite and micro peridotite, indicate a complex evolution in the magmatic plumbing system involving deeper zones of a heterogeneous mantle source. The picrite probably formed by mixing with a magma with a more primitive H2O and CO2 rich melt emplaced at 86 Ma ( 40Ar/39Ar data in amphibole). Contemporaneous trachytes, phonolites and alkali-feldspar dikes and SiO2-undersaturated and oversaturated syenite varieties, were emplaced into the upper crust cross cutting the Frade Layered Intrusive. All the described lithologies belong to the north sector of the Serra do Mar Province an represent a spatial and temporal association of a continuous bimodal magmatism that occurred in a short period of about 5 Ma.